UPAYA DIPLOMASI INDONESIA PADA PENINGKATAN INVESTASI ASING DI KOTA BATAM, PROVINSI KEPULAUAN RIAU (STUDI KASUS “Diplomatic Tour, Batam 7-9 September 2012”) - Apriliyanti, Romayati; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was made to explain about effort of Indonesian Diplomacy to improve the foreign investments in Batam City, the program is Diplomatic Tour at September, 7-9 September, 2012. Diplomatic Tour is a program of the Indonesia Foreign Ministry who promoted potential in some region in Indonesia to introduce up the world.The word of Diplomacy is from Ancient Greek Language, “Diploma”. The writer used Neoliberalism Theory. Theory of Location, and FDI consepth. Riau Island Province is a second foreign tourist gateway in Indonesia. The Province had two cities, they are Batam and Tanjung Pinang. Batam, Bintan, and Karimun are as Special Economic Zone in 2006, SEZ is a cooperation in placing one zone or more what ever investment and trade activity are done without intervention by local government, in other word local government only facilitator for investor through decreasing tax.One of advantage Diplomatic Tour program isi increasing the value of foreign investment in 2013 is rearch US$ 16,467,103,359,13. The Private Investments are more dominant than Government Investments.Keywords : Diplomacy, SEZ, Local, Investor, Diplomatic Tour